Identifikasi Risiko Ergonomi pada Pekerja Pendempulan Menggunakan Metode RULA untuk Mendeteksi Gangguan Musculoskeletal Disorders di CV XYZ - Hamidah, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Improper manual work can lead to musculoskeletal disorders (MSDs). CV XYZ, a company specializing in bodywork, faces MSD issues among its workers, but there is insufficient data on this matter. Contributing factors include the working environment and the inadequate use of assistive tools. The purpose of this research is to determine the key factors that contribute to MSDs, evaluate the level of risk involved, and offer suggestions for enhancing work posture through the Rapid Upper Limb Assessment (RULA) approach.The research involves bodywork workers at CV XYZ. The findings indicate the most common complaints are in the right shoulder (100%), lower back and buttocks (82%), right upper arm (76%), and lower neck (71%). Based on the RULA score (7), the workers' posture is classified as high risk, requiring immediate corrective actions. The proposed improvement is a workbench with a length of 57 cm and a height of 68 cm.